Uranium-series disequilibrium, sedimentation, diatom frustules, and paleoclimate change in Lake Baikal - Edgington, D. N.; Robbins, J. A.; Colman, S. M.; Orlandini, K. A.; Gustin, M. P. (Earth and Planetary Science Letters, 1996)
The large volume of water, approximately one-fifth of the total surface fresh water on the planet, contained in Lake Baikal in southeastern Siberia is distinguished by having a relatively high concentration of uranium (ca. 2 nM), and, together with the surface sediments, an unusually high U-234/U-238 alpha activity ratio of 1.95. About 80% of the input of 234 uranium to the lake, with a U-234/U-238 ratio of 2.0, comes from the Selenga River, Profiles of uranium, as well as the extent of isotopic disequilibrium in a 9 m sediment core collected on Academic Ridge, generally show high values during interglacial periods corresponding to high diatom frustule numbers (DiFr) and biogenic silica (BSi) data that have been reported elsewhere. During glacial periods (low DiFr and BSi), uranium progeny (U-234 and Th-230) were in secular equilibrium with low concentrations of their parent U-238. Radionuclide distributions were interpreted in terms of a quantitative model allowing for adsorption of riverine inputs of uranium onto two classes of sedimenting particles with differing U-238/Th-232 ratios and uranium progeny in secular equilibrium. If the U-234/U-238 activity ratio of adsorbed uranium has remained constant, mean sedimentation rates can be independently estimated as 3.6 +/- 0.6 and 3.7 +/- 0.9 cm . kyr(-1) for the decay of U-234 and in-growth of Th-230, respectively. These rates are consistent with a mean rate of 3.76 cm . kyr(-1), calculated by optimization of the correspondence between adsorbed U-238 and delta(18)O in dated oceanic sediments, The adsorbed uranium apparently tracks variable river flow during interglacials and is drastically reduced during periods of glaciation. Evidently, uranium has not been significantly redistributed within Baikal sediments over at least the past 250 kyr and is a unique, biologically non-essential, tracer for climate-sensitive processes, which provide their own internal geochronometers, potentially useful for ages up to 1 Myr BP.
Uz230Times Cited:61Cited References Count:29